KONSEP DIRI PADA INDIGO DEWASA AWAL - Maria Dini Prasetio (Universitas Katolik Widya Mandala Surabaya, 2019)
Indigo phenomenon in Indonesia at few moments have been trending topic in society. This phenomenon receive every positive or negative view of points in society. Indigo individuals are individual that have a differents potency for every indigo, which is ESP experience (Extrasensory Perception), sensitive, and rational. The purpose of this research is obtain a picture of the self concept’s development. This study uses a qualitative case study method through an interview on early adults aged 18-40 years old and have ESP experience (Extrasensory Perception) since child. There are two participants in this research. The analysis technique that used is inductive technique. This research use two kinds validity such as comunicative and argumentative validitas. Research result show that indigo individuals since child feels different between normal people. They feel special with their advantages and sometimes get different treatment with negative view from society and their family. The views and over-treatment related to their ability resulted indigo individuals not being open to their environment. Early adults who are indigo tend to be forced accept their advantages. Their self concept development influenced by their parents, family, and friendship environment. Early adults who are indigo saw indigo as a permanent ability, which couldn’t be eliminated or easily rejected.